The mystery of the last supper reconstructing the final days of Jesus - Humphreys, C. J. (Colin John), 1941- (Cambridge ; New York : Cambridge University Press, 2011)
"For centuries, we thought we knew what happened during Jesus' last days. Holy Thursday, Good Friday and Easter Sunday are not only observed by Christians around the world, but are also recognized in calendars and by non-practitioners as commemorating events in the final week of Jesus' life. But apparent inconsistencies in the Gospel accounts of this period have continued to puzzle Bible scholars -and fuel skeptics. In The Mystery of the Last Supper, Colin Humphreys uses science to reveal the truth about Jesus' final days. Reconciling conflicting biblical accounts with scientific evidence, Humphreys proves that the Gospels, correctly interpreted, are in remarkable agreement. He reveals the exact date of the Last Supper in a groundbreaking new timeline of Holy Week. Colin Humphreys is director of research at the Department of Materials Science and Metallurgy at the University of Cambridge. He is the author of The Miracles of Exodus (2003). He was awarded a knighthood in 2010 for services to Science"--
"This new book returns to this last theme and offers a detailed study of the associated puzzles caused by the apparent discrepancy between the Gospel of John and the other three Gospels on the date of the Last Supper of Jesus. Colin's solution is a new version of the old theory that different Jewish groups may have used different calendrical systems together with a proposal that Jesus held his meal not on the Thursday immediately preceding his crucifixion on the Friday but on the Wednesday evening, a view that allows a more adequate period of time for all the recorded events that have to be fitted in between the meal and the crucifixion"--
Machine generated contents note: Acknowledgements; 1. Three mysteries of the last week of Jesus; 2. Dating the crucifixion - the first clues; 3. The problem of the last supper; 4. Can we reconstruct the Jewish calendar at the time of Christ?; 5. The date of the crucifixion; 6. The moon will be turned to blood; 7. The Passover puzzle and the calendar of Moses; 8. Did Jesus use the solar Passover calendar of Qumran?; 9. The date of the last supper: the hidden clue in the synoptic gospels; 10. Was the Moses calendar used in Israel at the time of Jesus?; 11. The Galilean Passover and the date of the last supper; 12. From the last supper to the crucifixion; 13. The last days of Jesus: an overview; Bibliography; Index of modern authors; Index of Biblical and other ancient sources; General index.
Includes bibliographical references (p. [227]-233) and indexes.
Description based on print version record.
Keywords: Last Supper; Jesus Christ -- Chronology; Bible. -- Chronology; RELIGION / Biblical Studies / New Testament; RELIGION / Christian Theology / Christology; Electronic books